2008
DOI: 10.1007/s12274-008-8034-3
|View full text |Cite
|
Sign up to set email alerts
|

Imaging electronic structure of carbon nanotubes by voltage-contrast scanning electron microscopy

Abstract: We introduce voltage-contrast scanning electron microscopy (VC-SEM) for visual characterization of the electronic properties of single-walled carbon nanotubes. VC-SEM involves tuning the electronic band structure and imaging the potential profi le along the length of the nanotube. The resultant secondary electron contrast allows to distinguish between metallic and semiconducting carbon nanotubes and to follow the switching of semiconducting nanotube devices, as confi rmed by in situ electrical transport measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…Methods for measuring m-SWCNT content can be divided into bulk sample techniques and countingbased techniques. Counting-based techniques more accurately enumerate m-and sc-nanotubes and typically rely on their electrical and/or optical performance [20][21][22][23][24][25][26][27][28][29]. Although these methods give relatively accurate results, they involve tedious fabrication processes and costly instruments.…”
mentioning
confidence: 99%
“…Methods for measuring m-SWCNT content can be divided into bulk sample techniques and countingbased techniques. Counting-based techniques more accurately enumerate m-and sc-nanotubes and typically rely on their electrical and/or optical performance [20][21][22][23][24][25][26][27][28][29]. Although these methods give relatively accurate results, they involve tedious fabrication processes and costly instruments.…”
mentioning
confidence: 99%
“…15 In our devices, this was realized by grounding one of the two metal electrodes. The other electrode remained floating, albeit connected to the grounded electrode by the mSWNT.…”
mentioning
confidence: 99%
“…3c, it is found that the invisible CNTs in the SEM images are semiconducting ones, which is in consistence with previous studies. 28,[44][45][46][47][48] Obviously, our approach, which is not influenced by the electrical conductivity of the CNTs, provides a more accurate data on the number of the CNTs and represents a valuable complementor of the SEM technique.…”
Section: Resultsmentioning
confidence: 99%